Detection Antibiotic Resistance of Enviromental Bacterial Strains (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Antibiotics are randomly prescribed  for veterinary and human medication. Antibiotics by little number are used by human , animals are digested uncompletely  in their digestive system and ended up in communal sewage and hospitals, eventually discharge in environmental water sources directly with no processing.    Water itself consider as major factor of dispersal of bacteria between different environmental components. Besides, bacteria had  transferable genetic mobile elements to different sites of soil, water and humans.      Environmental swabs were collected locally including 50 swabs of hospital environment , 15 samples of poultry feces and chicken guts , 20 sample of heavy water and 15 sample of fish tank to identify16 isolate of Staphylococcus (4 isolate of Staphylococus aureus and 12 isolate of coagulase –ve Staphylococcus) , 19 isolate of Enterococcus spp. , 7 isolates of Pseudomonas and 5 environment isolates for each Shigella spp.  and Salmonella spp. .          Teicoplanin and Vancomycin sensitivity test of isolates was done , showing that 2out of 16 isolates of Staphylococcus (12.5%) were Vancomycin-resistant , and 3out of 19 isolates of Enterococcus (15.7 %) were Vancomycin-resistant, while the rest of isolates were Vancomycin- sensitive. From other side , all isolates was Teicoplanin- sensitive except only 1 Enterococcus spp. Isolate which was intermediate . The range of the Vancomycin MIC were (6-64) µg/ml . Vancomycin resistant isolates , showed that some isolates have one plasmid band after Extraction of their DNA.